The Effects of Oral 5-alpha Reductase Inhibitors on Penile Intracavernosal Pressures and Penile Morphology in Rat Model - Kilic, Sahin; Kolukcu, Engin; Erdemir, Fikret; Benli, Ismail; Arici, Akgul (Urology Journal, 2019)
Purpose: Benign prostatic hyperplasia (BPH), and erectile dysfunction (ED) are urological diseases which affect more than 50 % of men older than 50 years of age. It has been reported that 5-alpha-reductase inhibitors (5-ARIs) used in clinical studies for the treatment of BPH caused ED in 0.8-15.8% of the patients. The aim of this study is evaluation of the effects of oral finasteride and dutasteride on penile intracavernosal pressures and penile morphology in a rat model. Materials and Methods: Thirty Wistar Albino strain male rats were randomized into control (n = 10), finasteride (n = 10), and dutasteride (n = 10) groups. After 8 weeks of treatment erectile responses were evaluated in all rats measuring intracavernosal pressure (ICP) changes during erectile responses to cavernosal nerve electrical stimulation. Serum hormone levels were studied and all rats underwent prostatectomy and penectomy. All tissue samples were examined histomorphologically and a semiquantitative scoring system was used for cavernosal tissue collagen density grading. One-way analysis of variance was used for statistical analysis and P < .05 was accepted as the level of statistical significance. For two group comparisons Tukey HSD test was used as post hoc test of one way analysis of variance. Results: Approximately 50% decrease was seen in mean ICPs in the finasteride and dutasteride groups compared to the control group for all voltages (2.5 V, 5 V. 7.5 V). Mean ICPs for 7.5 V were 62.17 ± 30.89mmHg in control group, 35.27 ± 31.94 in the finasteride, and 36.01 ± 19.20mmHg in the dutasteride group. But regarding ICPs there was no statistically significant difference between the groups (P > .05). The serum testosterone (T) concentrations were higher in treatment groups (P < .001). Serum dihydrotestosterone (DHT), luteinizing hormone (LH) and follicle stimulating hormone (FSH) concentrations were not significantly different between the groups. As a result of histomorphological studies, a statistically significant increase in cavernosal tissue collagen density, and marked atrophic changes in prostatic epithelial tissues were observed in the treatment groups. Conclusion: Although 5-ARIs cause marked atrophic changes in prostatic epithelial tissues, and prominent collagen deposition in penile cavernosal tissues, no significant effect on penile ICPs was seen in this study. The failure to show a statistically significant difference was attributed to higher standard deviations of ICP values. If sample size and duration of the treatment are increased, statistically significant results in ICPs may be reached. The penile morphology evaluation results point to a negative effect of 5-ARIs on erectile function.